2023
DOI: 10.1021/acsami.3c12696
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Combustion of Magnesium Nanoparticles via Low-Temperature Plasma-Induced Hydrogenation

Brandon Wagner,
Minseok Kim,
Mahbub Chowdhury
et al.

Abstract: The hydrogenation of metal nanoparticles provides a pathway toward tuning their combustion characteristics. Metal hydrides have been employed as solid-fuel additives for rocket propellants, pyrotechnics, and explosives. Gas generation during combustion is beneficial to prevent aggregation and sintering of particles, enabling a more complete fuel utilization. Here, we discuss a novel approach for the synthesis of magnesium hydride nanoparticles based on a two-step aerosol process. Mg particles are first nucleat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 58 publications
(102 reference statements)
0
3
0
Order By: Relevance
“…相比之下, 固态的反应源种类更多、容易获 得. 借鉴高温气相转移技术, 一些低熔点金属元素能够 以气溶胶形式参与等离子体反应, 如镓 [87] 、锑 [88] 、 镁 [63,64] 、铋 [117] 、和铟 [118] 等, 为合理设计与固态反应源 相兼容的新型冷等离子体系统提出了新思路.…”
Section: 金属-绝缘体转变unclassified
“…相比之下, 固态的反应源种类更多、容易获 得. 借鉴高温气相转移技术, 一些低熔点金属元素能够 以气溶胶形式参与等离子体反应, 如镓 [87] 、锑 [88] 、 镁 [63,64] 、铋 [117] 、和铟 [118] 等, 为合理设计与固态反应源 相兼容的新型冷等离子体系统提出了新思路.…”
Section: 金属-绝缘体转变unclassified
“…For instance, Wagner et al. recently pointed out that the recombination of plasma-induced atomic hydrogen at the surface of Mg nanoparticles serves as the primary source of surface heating and actually hinders the full hydrogenation of the Mg particles because of the competing thermal decomposition of MgH 2 . Similarly, Lopez et al have shown, via in situ FTIR measurements, that hydrogen rapidly desorbs from silicon nanoparticles immersed in a nonthermal plasma because of rapid thermal desorption .…”
mentioning
confidence: 99%
“…The plasma density generally increases with the measured RF input power, resulting in an increase rate of energy transfer to plasma-exposed surfaces. The plasma exposure therefore could offer a unique pathway for heating adsorbates on catalysts in a different manner from any other conventional process. , It should be mentioned that multiple phenomena may contribute to this surface-targeted heating effect. Plasma-facing surfaces are exposed to fluxes of electrons, ions, and various electronically excited species.…”
mentioning
confidence: 99%
“…It should not be a surprise that a low-temperature process, i.e., one in which the gas temperature is close to room temperature, is also capable of producing graphite-like nanomaterials. This is consistent with our previous work on carbon nanoparticles and with several other publications on the processing of refractory materials in nonthermal plasmas. ,, Operation at mid- to low-pressure reduces heat losses to the background gas, and nanoparticles suspended in the plasma can reach very high temperatures because of exothermic reactions at their surfaces, resulting, for instance, in the formation of alloyed Si–Ge nanoparticles or the diffusion of hydrogen in magnesium to give MgH 2 nanoparticles. , …”
mentioning
confidence: 99%